Exploring adolescent academic stress in the digital and urban age: a mixed-methods study from CIT to checklist validation - Wang, Ruobing; Yang, Shengqin; Xu, Xiao; Mi, Shuaishuai; Hao, Na (Frontiers in Psychology, 2025)
IntroductionIn recent decades, middle and high school students have been experiencing increasing levels of academic stress. The reason may be rapid urbanization and the widespread use of the Internet, which have expanded students’ environments from the confines of family and school to the open community and cyber world. Greater exposure to academic information and social interactions may contribute to heightened stress levels. However, the underlying mechanisms remain underexplored. Furthermore, the current taxonomy of academic stress conflates self-stress with stress arising from social events, resulting in a misalignment between theoretical frameworks and measurement scales.Materials and methodsThe mixed-methods study explored stressful academic events among adolescents using the critical incident technique and validated a corresponding scale (Adolescent Stressful Academic Events Checklist, ASAEC). The study was conducted during the spring 2025 semester. In the qualitative phase, 84 participants, including teachers, parents, and students, were interviewed. Data were coded, member-checked, and analyzed to identify common stressful academic events. Based on these findings, a checklist of adolescent academic stress was developed, and its reliability and validity were examined through a survey of 453 adolescents.Results(1) Qualitative: The study categorized critical incidents from three dimensions (event topics, social actors, and interaction ways). A total of 540 critical incidents revealed common sources of academic stress related to enrollment, rivalry, career, working hard, intelligence, and social. These events were associated with various social actors, including neighbors, kinsmen, friends of parents, non-classmate peers, netizens, news media, self-media, parents, teachers, and classmates. Participants reported experiencing stress not only through direct interactions but also through mediated, observing, and distal interactions. (2) Quantitative: Both EFA and CFA supported a single-factor structure for the checklist. The Item Response Theory (IRT) model demonstrated strong psychometric properties, including high reliability, good model fit (as indicated by RMSEA, CFI, and TLI), and appropriate item parameters, infit indicators, and average information measures. ASAEC showed significant correlation with the hypothesized variables, confirming its criterion-related validity.Conclusion(1) Newly identified stressful academic events were found to be correlated with urban and online communities, and all related items were significant in the survey. These findings highlight the importance of considering the impact of digitalization and urbanization on academic stress. (2) Weak ties and new interaction ways were found to contribute to stressful academic events, while the checklist exhibited a single-factor structure. The findings suggest that the proposed three-dimensional framework requires further empirical validation. (3) ASAEC provides a reliable tool for assessing adolescent academic stress from an ecological perspective, facilitating more effective management that accounts for various interactions with a wide range of social actors.